EFFECT OF DOXORUBICIN AND DAUNORUBICIN ON THE ACTIVITY OF ACETYLCHOLINESTERASE IN ACUTE LYMPHOBLASTIC LEUKAMIA - Niazi, Iftikhar -ud-Din; Tariq, Shafiq Ahmed; Ali, Abid (Journal of Ayub Medical College Abbottabad, 2011)
Background: Our study was based on the alteration in the Michaelis Mentin parameters Apparent Michaelis Constant (aKm) and Apparent Maximum Velocity (aVm), which reflects activity of actylcholinesterase (AChE). This activity decreases in Acute Lymphoblastic Leukaemia (ALL). This decrease in aKm and aVm values shows bad prognosis. Similarly the anticancer drugs like Daunorubicin and Doxorubicin further decreases the aKm and aVm values which worsen the prognosis. The objective of this study was to determine and compare the extent of inhibition of Acetylecholine Esterase by Daunorubicin and Doxorubicin in ALL. Methods: Study of 100 patients including both male and female children who’s age ranged from 4 to 8 years and were advised doxorubicin and daunorubicin separately were tested by Ellman’s method using acetylcholine iodide as substrate and 5,5-dithiobis 2-nitrobenzine as a colour reagent regardless of dose regimen i.e. (once in 3 week, small dose per week or a continuous infusion for 72 to 96 hours. Results: In this study the Michaelis Mentin parameters Apparent Michaelis Constant (aKm) and Apparent Maximum Velocity (aVm) of the enzyme were estimated both in normal individuals and in the patients and also during treatment with daunorubicin and doxorubicin. The value of Michaelis Mentin parameters, aKm, aVm and percentage activity of the enzyme in normal individual are 23, 70, and 100 respectively. The values of aKm, aVm and percentage activity of the enzyme were also estimated in the patients before and after treatment. The values of aKm and aVm in patients of acute lymphoblastic leukaemia and percentage activity of enzyme is decreased. After the treatment with daunorubicin and doxorubicin the values and activity is further decreased. Conclusion: We conclude that the drugs under study both decrease the enzyme activity but daunorubicin inhibits the enzyme more than doxorubicin. Keywords: Doxorubicin, daunorubicin, acetylcholinestrase